Lying and insincerity - Stokke, Andreas (Oxford University Press, 2018)
Andreas Stokke presents a comprehensive study of the linguistic phenomenon of insincere language use, revealing how lying relates to 'bullshitting' and other forms of insincerity, and exploring the kinds of attitudes that go with insincere uses of language.